The Orphan's Tale - Jenoff, Pam (Don Mills, Ontario : Mira, 2017)
Sixteen-year-old Noa, forced to give up her baby fathered by a Nazi soldier, snatches a child from a boxcar containing Jewish infants bound for a concentration camp and takes refuge with a traveling circus, where Astrid, a Jewish aerialist, becomes her mentor.
Keywords: Circus -- Fiction; Teenage mothers -- Fiction; Jews -- Fiction -- Germany; World War, 1939-1945 -- Fiction -- Social aspects; France -- Fiction -- History -- German occupation, 1940-1945; Historical fiction